Actividades con germoplasma de frijol. Manejo de datos - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
During early 1986 computer programs were written to manage the expt. part of the bean database. In mid-year the programs were redesigned and recompiled to better access the data. In all, some 53 new dialogs were written to facilitate consultation of the bean database. All of the bean evaluation nursery and IBYAN data will be loaded together with passport and other data provided by the genetic resources unit. (CIAT)